Socjologiczne ujęcia kwestii narodu: podobieństwa i różnice - Górski, Piotr (Wydział Prawa i Administracji UAM, 1986)
The author discusses the peculiarity of the sociological approach to a. question of nation. That stands for treating it as a historically shaped form of collective Life. The author analyses the character of participation in a national community and the factors forming a national bond, i.e. territorial, economic, cultural political factors and the historical heritage of the community. The author emphasises, the importance of national consciousness as a factor able to form a nation on account of the embedded reflexive relation to territory, economics or state. Yet the most vital element of national consciousness is the historical feeling and national self-consciousness which is manifesting the approach to national community as the active, collective subject of the history. Thus in the conclusion the author advocates such definition of nation, which would emphasise its historical character, and the existing state and historical consciousness result in its forming into a community which is able to manage its destiny in a practical and intellectual way.
The Sociological Approach to a Question of Nation